Effect of Operating Costs, Sales Volume, Working Capital and Assets Turnover on Net Profit: Pengaruh Biaya Operasional, Volume Penjualan, Modal Kerja dan Perputaran Aktiva Terhadap Laba Bersih - Fais, Ainun; Dian, Imelda (Universitas Muhammadiyah Sidoarjo, 2018)
This study aims to determine the effect of operating expenses on net income, sales volume on net income, working capital on net income, asset turnover on net income and operating costs, sales volume, working capital and asset turnover simultaneously affecting the net income of food companies and beverages listed on the IDX for the 2014-2016 period. This research is a type of quantitative research, with the number of samples used, namely 10 food and beverage companies listed on the Stock Exchange for the 2014-2016 period. The analytical tool used is the analysis of multiple linear regression tests, coefficient of determination (R2), t test, F test and classic assumption test using SPSS version 20 for windows. The results of the study show that; 1) operational costs have a significant effect on net income, 2) sales volume has a significant effect on net income, 3) working capital has a significant effect on net income, 4) asset turnover has a significant effect on net income, and operating costs, sales volume, capital work and asset turnover have a significant effect on the net income of the company and beverages on the IDX for the period 2014-2016.